Rural-Urban Linkages of Dipayal-Silgadhi, Doti Municipality - Adhikari, Kamal (Research Journal, 2023)
This paper reports the findings of the study that examined the urban-rural relationship between Dipayal-Silgadhi, Doti Bazaar and the hinterland areas. Both primary and secondary sources of data were used and primary data were collected from a purposive sampling of 40 consumers and 30 service providers through structured questionnaire, field observation, and focus group discussion. Secondary data were collected from district and municipality profiles, journals, and e-resources. The study revealed that the highway connects Dipayal-Silgadhi, Doti with the hills and Tarai districts. It lies at a break-up point between the Tarai and Mountains areas of Sudurpaschim Province. The local traders have increased their functional magnitude with the coordination of Dhangadhi, Aateriya, and Mahendranagar. It provides functional services to the hinterlands of the northern, western, and eastern parts of Silgadhi. The opening of Samuhagad-Uditola, Shantinagar-Dang, Khaptad-Sadak, Kalena-Sadak, and Mallo-Kalena-Sadak has supported to access and expand the business, educational, and medical services in its hinterlands. However, with further extensions of highways, the buffering of hinterlands is shrinking to perform a variety of functions.